2015
DOI: 10.1002/asia.201500476
|View full text |Cite
|
Sign up to set email alerts
|

A Solution‐Processable Molecule using Thieno[3,2‐b]thiophene as Building Block for Efficient Organic Solar Cells

Abstract: A solution-processed acceptor-π-donor-π-acceptor (A-π-D-π-A) type small molecule, namely DCATT, has been designed and synthesized for the application as donor material in organic solar cells. The fused aromatic unit thieno[3,2-b]thiophene (TT) flanked with thiophene is applied as π bridge, while 4,8-bisthienyl substituted benzodithiophene (BDT) and 2-ethylhexyl cyanoacetate are chosen as the central building block and end group, respectively. Introduction of fused ring to the small molecule enhances the conjug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…A slight mismatch is observed versus the values determined by CV, which is suspected to derive from the lack of spatial considerations in the simulation. Wei et al 50 found that, for a small molecule donor using the same method as this study, the LUMO exhibits the largest error, which is similar to these ndings.…”
Section: Molecular Modelingsupporting
confidence: 83%
“…A slight mismatch is observed versus the values determined by CV, which is suspected to derive from the lack of spatial considerations in the simulation. Wei et al 50 found that, for a small molecule donor using the same method as this study, the LUMO exhibits the largest error, which is similar to these ndings.…”
Section: Molecular Modelingsupporting
confidence: 83%
“…In addition to the end-capped groups, the π-bridges also played critical roles in tuning the photovoltaic performance for small molecules. Yang et al synthesized S58 using thieno­[3,2- b ]­thiophene as the π-bridge . The introduction of thieno­[3,2- b ]­thiophene prolonged the conjugation length of the main chain and enhanced the π–π stacking, which facilitated the charge carrier transport.…”
Section: Bdt-based Photovoltaic Small Moleculesmentioning
confidence: 99%
“…Yang et al synthesized S58 using thieno [3,2b]thiophene as the π-bridge. 366 The introduction of thieno [3,2b]thiophene prolonged the conjugation length of the main chain and enhanced the π−π stacking, which facilitated the charge carrier transport. The S58-based SMSC device achieved a PCE of 5.20%.…”
Section: Electron-withdrawing Units Used In the Backbone Of Bdt-based...mentioning
confidence: 99%
“…Among them, the higher PCE presented in BDT-UF based OSC can be attributed to the more ideal conjugated structure formed by introducing alkyl-thiophene side chain with ortho-substituted "F" atom in end-capping group. In addition, based on the mian-chian engineering OCAR-TR-T-TR-BDT-TR-T-TR-OCAR, DCATT (2015) was designed by innovatively introducing TR-TT-TR as π-bridge unit; [371] SM-BDT (2021) was constructed by further extending the π-π conjugated plane. [372] Moreover, D(CATBTzT)BDT (2013) and CNRBDB (2014) were also synthesized by Chen et al [373] and Zhang et al [374] in turn, which were designed by adjusting the ratio of donor and acceptor units in the main-chain engineering.…”
Section: Ocar and Its Derivatives As End-capping Unitsmentioning
confidence: 99%